Loan Loss Provisioning Behaviour- An Empirical Study of Chinese Banks - Lyu, Tianyao (2017)
ABSTRACT The aim of this paper is to examine whether Chinese banking sector use loan loss provisions (LLPs) for earnings management, capital management, and whether there is a significant association between loan loss provisions and business cycle. In this paper, we introduced both X-efficiency and Z-score as independent variable to estimate LLPs. Thus, we utilized stochastic frontier approach to estimate X-efficiency and generalized method of moments to estimate LLPs. We analyzed annual data of 80 Chinese banks from 2008 to 2016 for 9 yeas. The empirical results indicate there is no income smoothing behaviour by using loan loss provisions in Chinese banking sector. As for capital management hypothesis, theoretically, if banks use loan loss provisions for capital management there would be a negative symbol of this coefficient. Hence, a positive relationship is insufficient to support that Chinese banks using LLP to manage capital. However, Chinese banks exhibit counter-cyclicality.